Towards UPnP-UP: Developing Context-Aware UPnP Applications - Sales, Thiago; Sales, Leandro; Almeida, Hyggo; Perkusich, Angelo (Anais do Simpósio Brasileiro de Computação Ubíqua e Pervasiva (SBCUP), 2009)
The Universal Plug-and-Play (UPnP) standard aims at connecting consumer electronics, intelligent appliances and mobile devices from many different vendors. Albeit providing a sophisticated solution for device and services discovery, UPnP control points and devices cannot communicate with each other by providing user and context sensitive information, preventing UPnP application developers from building smarter solutions for Pervasive Computing and allowing unauthorized users to grant access for UPnP resources. For this reason, this paper proposes an extension of the UPnP standard named UPnPUP, which allows user authentication and authorization mechanisms for the UPnP standard, maintaining backwards compatibility with previous versions of UPnP.